Planning of Sustainable Development of Tourism in Ukraine (On the Example of the Dnepropetrovsk Region) - Valentyna SHAPOVAL; Tetyana HERASYMENKO; Iryna KYRYLIUK; Tetiana BERBETS; Oksana LYTVYN (Communications of International Proceedings, 2020)
The article contains proposals for the creation of a system for managing territorial tourism based on a tourist organization with a developed structure of departments and certain management functions and the creation of a specialized information and tourist portal of the region in the Internet with a system for monitoring the tourist resources of territories in real time. A range of factors influencing on the tourist potential of the area is determined. A methodology for short-term planning of the development of domestic tourism has been developed and tested based on optimization of regional budgets investments. Research lies in clarifing and expanding the interpretation of the concept of “tourist territory”, taking into account the rationale for the creation and maintenance of a management system, the construction of a factorologic model of tourism potential, including the coefficients of significance of the main factors of tourism development. The developed proposals and recommendations allow the regional authorities to objectively assess the level of development of domestic tourism in the region, analyze processes and determine trends in domestic tourism, as well as the directions and scale of its development, rationally and effectively spending budgetary funds.
Keywords: Enterprise of tourist complex; maximization of tourist potential; tourist territories; investments; management.